(untitled) (Bangladesh Journal of Psychiatry, 2022)
Schizoid personality disorder is a rare type of personality disorder that is characterized by restricted range of expression of emotions such as emotional coldness, detachment or flattened affectivity to almost each and everything in daily and natural activities. This was a case report about a 30 year old male from a rural area who presented with the complaints of being self absorbent, slothful, reluctant with self-laughing, self-muttering and odd behavior, having little interest in emotional reaction with poor social interactions and no interest in earning or pleasurable activities. On mental state examination his mood was found to be euthymic with restricted affect; decreased rate and rhythm of speech with impairment of judgement, abstract and insight. Other medical causes of such conditions were excluded. In addition to pharmacological treatment, psychological interventions were exercised and considerable improvement was noticed. Bang J Psychiatry 2022;36(2): 42-43